Biocontrol characteristics of wild basidiomycetes and their applicability to suppress rice blast fungus, Magnaporthe oryzae / Adil Fikri Jumiry - Jumiry, Adil Fikri (Faculty of Plantation and Agrotechnology, 2018)
Rice (Oryza sativa) is the staple food and a source of income for farmers in Malaysia. Rice blast disease caused by fungus Magnaporthe oryzae significantly reduces rice production and cause economic loss to the grower. In fact, rice blast disease cause by fungus Magnaporthe oryzae can affect all the above ground part of paddy plant, especially at leaf, node, grains and panicle and sometimes at leaf sheath. This study attempts to investigate the antagonistic effects of the wild basidiomycetes against Magnaporthe oryzae and to examine the fungicidal or antifungal activity of basidiomycetes against the causal agent of rice blast disease, M.oryzae. A total of five different kinds of basidiomycetes isolates (CS1, CS2, CJBBB, CPP2 and CBC) were tested in this study. In vitro studies, dual culture assays were done by growing each of the wild basidiomycetes isolates against M.oryzae culture on a same PDA to observe the antagonistic effect of each wild basidiomycetes isolate. The effectiveness of the wild basidiomycetes in inhibiting the development of M.oryzae colonial growth was determined by using Percentage Inhibition Radial Growth (PIRG).Wild basidiomycetes isolates CS2 and CPP2 shown the highest percentage of PIRG which means both of them are the most effective wild basidiomycetes in inhibiting the mycelial growth of M.oryzae for in vitro studies. For in vivo studies, healthy rice plants were inoculated with M.oryzae. After a week, the infected rice plants were treated with the culture filtrates from wild basidiomycetes CS2, CPP2 and CJBBB. The data received from the research were recorded and further analyzed using statistical analysis. Based on in vivo studies, wild basidiomycete CJBBB has anti – phytofungal properties that can inhibit the development of blast disease on rice leaves.